2011
DOI: 10.1161/circulationaha.110.002832
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Defects and Developmental and Other Psychiatric Disorders

Abstract: Background— We examined the risk of psychiatric in-patient admissions and out-patient visits among Danish patients with congenital heart defects (CHD). Methods and Results— Using the Danish National Registry of Patients, we identified CHD patients born January 1, 1977, to January 1, 2002. For each patient, we randomly selected 10 population-comparison cohort members from the Danish Civil Registration System, matched by sex and birth year. We computed cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…Our findings extend the knowledge of long-term neurological impairment and mental health functional morbidities in the population with CHD. Although previous studies have reported elevated risks of adverse neurodevelopmental outcomes among individuals with CHD, including increased occurrence of depression, autism, and epilepsy compared with the general population, [6][7][8]19,[32][33][34][35] our study examined an older adult population to determine the later-life consequences of this neurological outcome. Although the underlying pathophysiological mechanisms are not completely understood, the potential etiologic factors appear multifactorial and consistent with previous findings within the neurodevelopmental scientific literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings extend the knowledge of long-term neurological impairment and mental health functional morbidities in the population with CHD. Although previous studies have reported elevated risks of adverse neurodevelopmental outcomes among individuals with CHD, including increased occurrence of depression, autism, and epilepsy compared with the general population, [6][7][8]19,[32][33][34][35] our study examined an older adult population to determine the later-life consequences of this neurological outcome. Although the underlying pathophysiological mechanisms are not completely understood, the potential etiologic factors appear multifactorial and consistent with previous findings within the neurodevelopmental scientific literature.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Neurodevelopmental deficits among infants and children with CHD are well described. [6][7][8] However, research on long-term neurological outcomes in adults with CHD is more limited. Dementia is among the most important late-life neurological diseases in the general population.…”
mentioning
confidence: 99%
“…In accordance with previous studies, unspecific codes of CHD, codes not related to CHD, and codes of nonstructural CHD were not categorized as CHD. 25,26 Furthermore, isolated bicuspid aortic valve, isolated patent ductus arteriosus, aortic insufficiency, mitral insufficiency, and minor atrial septal defects, including persistent foramen ovale, were not categorized as CHD. The use of the diagnoses has been validated previously.…”
Section: Congenital Heart Defectsmentioning
confidence: 99%
“…This register has been shown previously to be a reliable and valid source for identifying congenital heart disease malformations, [10][11][12][13] and it has been used extensively in clinical epidemiological studies of congenital heart defects. [14][15][16][17][18] In the present study, we identified >500 congenital heart defect cases among both twins and singletons, which allowed for subanalyses of specific congenital heart defects restricted to, for example, operated congenital heart defect cases. Information from the Danish Twin Registry [19][20][21] provided information about zygosity of the twins, thereby also enabling us to make inferences about the impact of chorionicity.…”
Section: Editorial See P 1173 Clinical Perspective On P 1188mentioning
confidence: 99%